Features of Conflict Management in the Labor Team of Industrial Enterprise - Rovenska, V. V.; Ровенська, В. В. (Державний заклад «Луганський національний університет імені Тараса Шевченка»; Інститут економіки промисловості НАН України, 2020)
The article analyzes the nature of conflicts and their classification. The typology of creative employees according to Isaksen and Dorval is presented. It is revealed that the conflict is an important form of interaction between people and serves as a means of solving many problems. It is proved that for the choice of an adequate method of influence and management of the corresponding conflict it is expedient to carry out classification depending on the basic signs: a way of the decision; spheres of manifestation; direction of influence; degree of expressiveness; number of participants; impaired needs. The causes of destructive conflicts at the industrial enterprise are determined. Methods of conflict management in the labor collective of an industrial enterprise are presented, as well as the main technologies of conflict management are considered.

У статті проведено аналіз природи виникнення конфліктів та їхня класифікація. Представлено типологію креативних співробітників за Ісаксеном та Дорвалем. Виявлено, що конфлікт є важливою формою взаємодії між людьми і слугує засобом вирішення багатьох проблем. Доведено, що для вибору адекватного методу впливу й управління відповідним конфліктом доцільно проводити класифікацію залежно від основних ознак: спосіб вирішення; сфери прояву; спрямованості впливу; ступеня виразності; кількості учасників; порушених потреб. Визначено причини виникнення деструктивних конфліктів на промисловому підприємстві. Представлено методи управління конфліктами у трудовому колективі промислового підприємства, а також розглянуто основні технології регулювання конфлікту.
Keywords: conflicts; labor collective; conflict management; causes of conflicts; conflict management technologies; конфлікти; трудовий колектив; управління конфліктами; причини виникнення конфліктів; технології регулювання конфлікту